MDA5 ISGylation is crucial for immune signaling to control viral replication and pathogenesis - Lucky Sarkar; GuanQun Liu; Dhiraj Acharya; Junji Zhu; Zuberwasim Sayyad; Michaela U. Gack (Proceedings of the National Academy of Sciences, 2025)
The posttranslational modification (PTM) of innate immune sensor proteins by ubiquitin or ubiquitin-like proteins is crucial for regulating antiviral host responses. The cytoplasmic dsRNA receptor melanoma differentiation-associated protein 5 (MDA5) undergoes several PTMs including ISGylation within its first caspase activation and recruitment domain (CARD), which promotes MDA5 signaling. However, the relevance of MDA5 ISGylation for antiviral immunity in an infected organism has been elusive. Here, we generated knock-in mice (MDA5 K23R/K43R ) in which the two major ISGylation sites, K23 and K43, in MDA5, were mutated. Primary cells derived from MDA5 K23R/K43R mice exhibited abrogated endogenous MDA5 ISGylation and an impaired ability of MDA5 to form oligomeric assemblies, leading to blunted cytokine responses to MDA5 RNA-agonist stimulation or infection with encephalomyocarditis virus (EMCV) or West Nile virus. Phenocopying MDA5 −/− mice, the MDA5 K23R/K43R mice infected with EMCV displayed increased myocardial injury and mortality, elevated viral titers, and an ablated induction of cytokines and chemokines compared to WT mice. Molecular studies identified human HERC5 (and its functional murine homolog HERC6) as the primary E3 ligases responsible for MDA5 ISGylation and activation. Taken together, these findings establish the importance of CARD ISGylation for MDA5-mediated RNA virus restriction, promoting potential avenues for immunomodulatory drug design for antiviral or anti-inflammatory applications.